An Emerging Technique For Poorly Soluble Drugs: Self Emulsifying Drug Delivery System - Patel, Neelam D (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTUp to 40% of new chemical entities discovered by the pharmaceutical industry are poorly soluble or lipophilic compounds, which leads to poor oral bioavailability. Currently a number of technologies are available to deal with the poor solubility, dissolution rate and bioavailability of insoluble drugs. Recently much attention has been paid to lipid based formulations with particular emphasis on self emulsifying drug delivery system (SEDDS), to improve the oral bioavailability of lipophilic drugs. Self-micro emulsifying formulations are mixtures of oils and surfactants, ideally isotropic, and sometimes containing co-solvents, which emulsify spontaneously to produce fine oil-in-water emulsion when introduced into aqueous phase under conditions of gentle agitation. The digestive motility of the stomach and intestine provide the agitation necessary for self-emulsification in vivo. The present review describes various formulation components, mechanism of self emulsification, biopharmaceutical aspects, characterization methods and applications of self emulsifying drug delivery system.